2011
DOI: 10.1002/hep.24157
|View full text |Cite
|
Sign up to set email alerts
|

Human hepatic stem cell and maturational liver lineage biology

Abstract: Livers are comprised of maturational lineages of cells beginning extrahepatically in the hepato-pancreatic common duct near the duodenum and intrahepatically in zone 1 by the portal triads. The extrahepatic stem cell niches are the peribiliary glands deep within the walls of the bile ducts; those intrahepatically are the canals of Hering in postnatal livers and that derive from ductal plates in fetal livers. Intrahepatically, there are at least 8 maturational lineage stages from the stem cells in zone 1 (perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
280
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 278 publications
(297 citation statements)
references
References 65 publications
9
280
0
3
Order By: Relevance
“…2C, middle) were coexpressed with CK19, a well-known marker for HSCs and cells of the cholangiocyte lineage. 24 Moreover, HAI-1 was also coexpressed with epithelial cell adhesion molecule (EpCAM), Gli-2, and OV6, additional biomarkers for HSCs (Supporting Fig. 3A-C).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…2C, middle) were coexpressed with CK19, a well-known marker for HSCs and cells of the cholangiocyte lineage. 24 Moreover, HAI-1 was also coexpressed with epithelial cell adhesion molecule (EpCAM), Gli-2, and OV6, additional biomarkers for HSCs (Supporting Fig. 3A-C).…”
Section: Resultsmentioning
confidence: 96%
“…3D), which probably represent a subset of HSCs. 15,24 Thus, we hypothesized that HAI-1 and/ or -2 may also have functions in HSCs. To prove this, we examined HAI expression in the developing livers of legally aborted fetuses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 However, albumin and transthyretin are expressed in cells undergoing liver differentiation from embryoid bodies 6 and in hepatic and biliary tree stem/progenitors in intrahepatic (canals of Hering) and/or extrahepatic (peribiliary glands) niches. 7,8 In the studies by Dill et al, 1 biliary hyperplasia and large biliary cyst formation were induced, even though the albumin gene promoter was targeted to induce selective hepatic N2ICD overexpression. Therefore, albumin-expressing cells in different anatomical sites could have been targeted.…”
Section: To the Editormentioning
confidence: 99%
“…Although EpCAM is known to be expressed in a variety of normal epithelial cells, it is strongly overexpressed in human adenocarcinomas [7]. In liver cell lineages, EpCAM is absent in mature hepatocytes but detectable in hepatic stem/progenitor cells and cholangiocytes [8]. Numerous studies have suggested the utility of EpCAM as a marker to identify liver cancer stem cells as well as normal hepatic progenitors [3].…”
mentioning
confidence: 99%